PERAN BAHASA INDONESIA DALAM PENERAPAN NILAI-NILAI KARAKTER PADA ANAK USIA DINI - Yenni Fitria; Juwita Juwita (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
Indonesia Language has an important role in implication of character values to early chilhood because Indonesia Language is used as a tool for the dissemination and absorption of knowledge, tools for self-development in general, tools for thinking reasoning, communication tools and socio-cultural development and educational tools. By using qualitative descriptive method, the function of language as a communication tool and teacher's self-expression in the classroom gives an overview of the use of verbal and nonverbal language teachers of early childhood education in the classroom clearly seen. The speech used by the teacher influences students to apply character values in the form of politeness in language. The use of polite verbal and nonverbal language can help teachers of early childhood education in the application of character values.